A sinter-free future for solid-state battery designs. Issue 7 (17th June 2022) - Hood, Zachary D.; Zhu, Yuntong; Miara, Lincoln J.; Chang, Won Seok; Simons, Philipp; Rupp, Jennifer L. M.
Abstract : The newly developed sequential decomposition synthesis (SDS) method permits the fabrication of ceramic solid electrolytes with thickness close to today's polymer separators and offers opportunities to obtain the desired phase at reduced temperatures. Abstract : Ceramic-based solid electrolytes and separators are particularly attractive for use in next-generation batteries as a way to increase the electrochemical stability window and improve safety. However, batteries with higher energy densities require thin membranes comparable in thickness to the polymer separators ( e.g., 10–25 μm) found in today's Lithium-ion batteries. To date, conventional ceramic–electrolyte processing routes have not been able to achieve this goal as they typically operate on the principle of sintering: going from particle to a densified ceramic body. To overcome this challenge, we provide a blueprint for an alternative cost-effective sequential decomposition synthesis (SDS) approach that uniquely accesses the thickness range required from solid Li oxide-based electrolytes close to those of today's polymer separators and offers immense opportunities for to obtain the desired phase at significantly lower processing temperatures (<700 °C) with unique ceramic microstructures. We specifically highlight the SDS processing of Li garnets and disclose basic SDS precursor and ceramic processing concepts that can be adapted to other Li-containing oxides.